Glycogen production for biofuels by the euryhaline cyanobacteria Synechococcus sp. strain PCC 7002 from an oceanic environment - Aikawa, Shimpei (BioMed Central, 2014)
BACKGROUND: Oxygenic photosynthetic microorganisms such as cyanobacteria and microalgae have attracted attention as an alternative carbon source for the next generation of biofuels. Glycogen abundantly accumulated in cyanobacteria is a promising feedstock which can be converted to ethanol through saccharification and fermentation processes. In addition, the utilization of marine cyanobacteria as a glycogen producer can eliminate the need for a freshwater supply. Synechococcus sp. strain PCC 7002 is a fast-growing marine coastal euryhaline cyanobacteria, however, the glycogen yield has not yet been determined. In the present study, the effects of light intensity, CO(2) concentration, and salinity on the cell growth and glycogen content were investigated in order to maximize glycogen production in Synechococcus sp. strain PCC 7002. RESULTS: The optimal culture conditions for glycogen production in Synechococcus sp. strain PCC 7002 were investigated. The maximum glycogen production of 3.5 g L(−1) for 7 days (a glycogen productivity of 0.5 g L(−1) d(−1)) was obtained under a high light intensity, a high CO(2) level, and a nitrogen-depleted condition in brackish water. The glycogen production performance in Synechococcus sp. strain PCC 7002 was the best ever reported in the α-polyglucan (glycogen or starch) production of cyanobacteria and microalgae. In addition, the robustness of glycogen production in Synechococcus sp. strain PCC 7002 to salinity was evaluated in seawater and freshwater. The peak of glycogen production of Synechococcus sp. strain PCC 7002 in seawater and freshwater were 3.0 and 1.8 g L(−1) in 7 days, respectively. Glycogen production in Synechococcus sp. strain PCC 7002 maintained the same level in seawater and half of the level in freshwater compared with the optimal result obtained in brackish water. CONCLUSIONS: We conclude that Synechococcus sp. strain PCC 7002 has high glycogen production activity and glycogen can be provided from coastal water accompanied by a fluctuation of salinity. This work supports Synechococcus sp. strain PCC 7002 as a promising carbohydrate source for biofuel production.